Pemberdayaan Kepada Masyarakat tentang Budidaya Bawang Merah di Desa Sungai Pinang Kecamatan Kubu Babussalam - Syafrinal, Syafrinal; Ardian, Ardian; Khoiri, Amrul; Silvina, Fetmi; Nurbaiti, Nurbaiti; Yoseva, Sri; Wulandari, Chicha (Unri Conference Series: Community Engagement, 2024)
Shallots are a commodity that people need to use as a food flavoring and other things whose availability in Riau is still lacking and are imported from neighboring provinces such as West Sumatra, Brebes and others, and this is an opportunity for farmers in Riau to cultivate shallots. The success of a shallot growing business is determined by the knowledge and skills of how to grow shallots, for this reason there is a need for community service activities, Community Empowerment regarding Shallot Cultivation in Sungai Pinang Village, Kubu Babussalam District. Community empowerment through shallot cultivation in Sungai Pinang Village, Kubu Babussalam District aims to increase farmer knowledge and skills as well as farmer welfare regarding shallot cultivation.